A treasury of mermaids : mermaid tales from around the world [book review] - Rabner, Lanell (1998)
Climo, Shirley. A Treasury of Mermaids: Mermaid Tales from Around the World. Illustrated by Jean Tseng and Mou-sein. HarperCollins, 1997. ISBN 0-06-023876-3. $16.95. 75 pp.” All PB NF Reviewed by Lanell Rabner Merfolk have long captured the imagination of people around the world. They are simply water people whose home is the mere--a sea, lake, river, spring, or merely a swampy place. They are thought to be wise and to possess irresistible voices. Renowned folklorist Shirley Climo has drawn from mermaid lore worldwide to present this enchanting definitive collection of merpeople--from the Irish merrow and Swiss nix to the ancient Greek Siren and Eskimo nuyaqpalik. These stories speak to the magic of the water sprites and the fortunes or fates of those who dare try to possess them. Woven together with insightful introductions, Climo discusses myths from many countries, presenting age-old tales from Europe along with only recently recorded tales from other regions. Stunning paintings complement the storytelling, creating an enchanting feast for the imagination. 75 p. : col. ill. 29 cm. Children's Book and Play Review, May / June 1998